Opposition political parties and democratic consolidation in Nigeria: examining All Progressive Congress (APC) in the 2015 general elections - Sule, Babayo; Mohd Sani, Mohd Azizuddin; Mat, Bakri (Airiti Inc., 2018)
Opposition political parties in Nigeria have been battling with the politics of zero sum game where winner takes all and loser lose all in a democratic setting since political independence in 1960. The ruling party used powers of incumbency, state treasury, state apparatus and all advantages of power to emasculate and dominate the political arena. This paper examined the role that All Progressive Congress (APC) played differently from the previous opposition parties in the country during the 2015 General Elections. The methodology adopted is the use of qualitative data analysis where selected informants from the categories of stakeholders associated with the subject of study were interviewed. The research concludes that but, for the significant role played by APC in challenging the ruling PDP in the 2015 General Elections, Nigeria would have turned into an official one party system with a choiceless democracy. The research recommends that, opposition political parties need to form a platform of merger to be stronger the way APC did in 2015 and also a level playing ground should be provided for all parties to contest freely in addition an improvement in the electoral system in general.